2011
DOI: 10.1007/s00296-011-2175-5
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin and RANKL in the pathogenesis of rheumatoid arthritis-induced osteoporosis

Abstract: Osteoporosis represents an important cause of morbidity in adult rheumatoid arthritis (RA) patients who exhibit increased fracture risk. It is thought that osteoclast and its dysfunction which mediated by many cytokines are the principal pathogenesis of this bone disease, although the mechanisms are still not fully understood. Osteoprotegerin (OPG) and receptor activator of nuclear factor-kappa B ligand (RANKL) have been revealed in the pathogenesis of primary osteoporosis and other metabolic bone diseases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 32 publications
8
63
1
3
Order By: Relevance
“…Chronic inflammation from the disease affects bone metabolism, disrupting the normal cycle of bone resorption and repair, leading to local and generalized bone loss [4]. The mechanism of bone loss in RA patients is still unclear, but it is believed to be related to an imbalance in the ratio of receptor activator of NF-kB ligand and osteoprotegerin [4]. Osteoporosis, a major risk factor for fracture, represents an important co-morbidity for RA patients and other rheumatologic diseases, such as systemic sclerosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation from the disease affects bone metabolism, disrupting the normal cycle of bone resorption and repair, leading to local and generalized bone loss [4]. The mechanism of bone loss in RA patients is still unclear, but it is believed to be related to an imbalance in the ratio of receptor activator of NF-kB ligand and osteoprotegerin [4]. Osteoporosis, a major risk factor for fracture, represents an important co-morbidity for RA patients and other rheumatologic diseases, such as systemic sclerosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al 21 found that age and CRP concentrations were identified as the crucial risk determinants of osteoporosis in RA. Also in our study we found that ESR, CRP and age were positively correlated with serum RANKL levels in RA.…”
Section: Disscussionmentioning
confidence: 99%
“…On the other hand, osteoblasts produce osteoprotegerin (OPG), a decoy receptor for RANKL, and function as bone-forming cells (6,15,24). In fact, RANKL/OPG ratio is elevated in the synovial tissue/fluid in patients with untreated RA (14). Other mediators, such as osteopontin (OPN), osteocalcin (OCN) and insulin-like growth factor (IGF)-I also influence bone remodeling.…”
mentioning
confidence: 99%
“…over bone formation (10,(13)(14)(15). IL-17 is a major cytokine driving osteoclastogenesis leading to bone resorption (8,12,26).…”
mentioning
confidence: 99%